Tolerance Limits of Cruelty in the Philosophy of the 20th Century: The Possibility of an Ambivalent Interpretation - Borodina, N. V.; Melnyk, Y. M. (Anthropological Measurements of Philosophical Research, 2024)
Purpose. The research explores the ambivalent interpretations of the tolerance limits of cruelty in 20th-century philosophy. Theoretical basis. The research is based on the concepts of Jean-Paul Sartre, Georges Bataille, and Albert Camus, who do not justify cruelty but demonstrate its potential legitimacy under certain circumstances. Originality. The authors have identified three main perspectives on tolerating cruelty, which form the foundation for an ambivalent interpretation. These perspectives include the justification of cruelty as necessary in the struggle for social justice (Sartre), the justification of cruelty towards oneself as a consequence of human rights and freedoms (Camus), and the justification of epistemological cruelty as a means to expand the boundaries of knowledge (Bataille). Conclusions. The ambivalent interpretation of cruelty, as exemplified by Bataille, Camus, and Sartre, blurs the tolerance limits of cruelty and creates opportunities for manipulations that may infringe upon people’s rights and freedoms. If Camus’s concept remains within the limits of respect for human dignity, then in Sartre’s interpretation, a person can be perceived as a tool for social struggle, and in Bataille – as an opportunity to gain a new ecstatic experience through cruel treatment of others.